Polygonatum kingianum polysaccharide alleviated intestinal injuries by mediating antioxidant ability and microbiota - Qiu, Reng; Pan, Chuangye; Qin, Yuxi; Wei, Qianfei; Yu, Yue; Zhang, Ying; Xie, Xuehan; Li, Jianqin; Chen, Shouhai; Li, Kun; Fouad, Dalia; Wu, Yi; et al. (Frontiers in Microbiology, 2025)
IntroductionPolygonatum kingianum is a well-known medicinal herb with proven bioactivities; however, little is known about the effects of its polysaccharide on intestinal injuries in animals induced by lipopolysaccharide (LPS).MethodsA total of 30 Institute of Cancer Research (ICR) mice were divided into control (CH), induced (MH), and treated (H) groups. Mice in group H were supplemented with 100 mg/kg Polygonatum kingianum polysaccharides, while groups C and M were treated with the same amount of normal saline by gavage for 18 days. On the 18th day animals in groups M and H were induced by LPS (10 mg/kg).ResultsThe results showed the weight of mice in group MH significantly dropped (P < 0.0001), while mice in the PK group had a higher weight (P < 0.01). Pathological analysis found that the majority of the villi in mice induced by LPS were broken and short, while PK-treated animals had longer and considerably integrated villi. The villi length in groups CH (P < 0.0001) and H (P < 0.0001) was longer than that in group M, and the value of villi length/crypt depth in group MH was smaller than that in groups CH (P < 0.0001) and H (P < 0.0001), while the crypt depth in group MH was higher than in groups CH (P < 0.0001) and H (P < 0.0001). Serum inspection showed that MAD (P < 0.05), IL-1β (P < 0.05), IL-6 (P < 0.05), and TNF-α (P < 0.01) were significantly higher in group MH, while SOD (P < 0.001), T-AOC (P < 0.01), and GSH-Px (P < 0.01) were notably higher in groups CH and H. Microbiome sequencing of mice obtained 844,477 raw and 725,469 filtered reads. There were 2,407 ASVs detected in animals, and there were 312 and 328 shared ASVs between CH and MH, and CH and H, respectively. There were 5 phyla and 20genera of remarkable bacteria found among mice groups including genera of Escherichia, Pseudomonas_E, Mailhella, Paramuribaculum, NM07-P-09, Odoribacter, Nanosyncoccus, SFM01, Onthenecus, Clostridium_Q, UBA6985, Ructibacterium, UBA946, Lachnoclostridium_B, Evtepia, CAG-269, Limivicinus, Formimonas, Dehalobacterium, Dwaynesavagella, and UBA6985. We revealed that Polygonatum kingianum polysaccharide could alleviate intestinal injuries by promoting oxidation resistance, decreasing inflammatory responses, and accommodating the intestinal microbiota of mice.DiscussionOur results suggest the possibility of developing novel therapies for intestinal diseases.